Sustaining cerebral perfusion in intracranial atherosclerotic stenosis: The roles of antegrade residual flow and leptomeningeal collateral flow. Issue 1 (January 2020) - Lan, Linfang; Leng, Xinyi; Ip, Vincent; Soo, Yannie; Abrigo, Jill; Liu, Haipeng; Fan, Florence; Ma, Sze Ho; Ma, Karen; Ip, Bonaventure YM; Chan, Ka Lung; Mok, Vincent CT; et al.
We aimed to investigate the roles of antegrade residual flow and leptomeningeal collateral flow in sustaining cerebral perfusion distal to an intracranial atherosclerotic stenosis (ICAS). Patients with apparently normal cerebral perfusion distal to a symptomatic middle cerebral artery (MCA)-M1 stenosis were enrolled. Computational fluid dynamics models were built based on CT angiography to obtain a translesional pressure ratio (PR) to gauge the residual antegrade flow. Leptomeningeal collaterals (LMCs) were scaled on CT angiography. Cerebral perfusion metrics were obtained in CT perfusion maps. Among 83 patients, linear regression analyses revealed that both translesional PR and LMC scale were independently associated with relative ipsilesional mean transit time (rMTT). Subgroup analyses showed that ipsilesional rMTT was significantly associated with translesional PR ( p < 0.001) rather than LMC scale in those with a moderate (50–69%) MCA stenosis, which, however, was only significantly associated with LMC scale ( p = 0.051) in those with a severe (70–99%) stenosis. Antegrade residual flow and leptomeningeal collateral flow have complementary effects in sustaining cerebral perfusion distal to an ICAS, while cerebral perfusion may rely more on the collateral circulation in those with a severe stenosis.